레반 Diet 섭취에 의한 한국 여성의 체지방 축적 억제와 혈중 지질의 개선 효과 - 강순아(Soon Ah Kang); 장기효(Ki-Hyo Jang); 이재철(Jae-Cheol Lee); 장병일(Byung-Il Chang); 임영애(Young Ae Lim); 송병춘(Byeng Choon Song) (Korean journal of community nutrition, 2003)
This study was performed to investigate the effects of a levan diet on the body fat accumulation and serum lipid composition of 29 Korean women over a period of up to 12 weeks (n=13 for the control group, n=16 for the levan group). The subjects ate an uncooked diet (6 g) with 400$m\ell$ of tap water twice a day. The mean body weight and height measurements of the subjects (levan group) at the outset were 66.0$±$8.8kg and 156.7$±$5.3cm, respectively. The subjects showed a significant reduction in weight, body fat mass, anthropometric measurements and skinfold thickness during the experimental period. The waist hip ratio (WHR) was 0.88$±$0.03 at the outset, and fell to 0.82$±$0.05 after 4 weeks. The intake of levan was also influenced on the levels of serum Fe, leptin, lipoprotein lipase, HDL-cholesterol, LDL-cholesterol, and triglyceride. The serum glucose levels were within the normal range during the experimental period. The initial serum triglyceride level was 121mg/dl, but fell to 103mg/dl after 4 weeks of levan supplementation. The current study demonstrates that a levan diet is effective in controlling weight, body fat, HDL-cholesterol, LDL-cholesterol, and triglyceride levels.